Argument on behalf of Great Britain [electronic resource]. - Bering Sea Claims Commission. ([Washington? : G.P.O.?, 1897)
Vol. V. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14456-14461. Includes: Argument for the United States in reply and a final Argument on behalf of Great Britain in reply. At head of title: Behring Sea Claims Commission. Electronic reproduction. Mode of access: Internet. 44